Method for preparing battery-grade iron phosphate and lithium carbonate from waste positive electrode material

Through acid leaching, extraction and copper removal, ammonium sulfate removal and aluminum removal, combined with lime removal and evaporation and lithium extraction, the problems of large impurity removal pressure and low recovery rate of valuable metals in the recycling of waste lithium iron phosphate batteries are solved, achieving high efficiency Full recovery and zero wastewater discharge, and product purity and recovery rate are significantly improved.

CN119118083AActive Publication Date: 2024-12-13GANZHOU TENGYUAN COBALT INDAL

Patent Information

Application Number
CN202411398971.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-13
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

There are problems in the recycling technology of existing waste lithium iron phosphate batteries with high impurity removal pressure, low recovery rate of valuable metals and large process solutions, making it difficult to achieve efficient full recovery of iron phosphate and lithium carbonate.

Method used

Using the process of acid leaching, extraction and removal of copper, ammonium sulfate, aluminum removal, adjustment of iron-phosphorus ratio, oxidation and synthesis of iron phosphate, aging and washing, lime removal, evaporation and concentration of lithium extraction, sodium carbonate precipitation of lithium, and carbonized resin calcium and magnesium removal, etc., Recycling solution and evaporation concentration achieve zero discharge of wastewater, deeply remove impurities, and improve recovery and purity.

Benefits of technology

The efficient recycling of valuable elements such as iron, phosphorus, and lithium in waste lithium iron phosphate positive electrode materials has been achieved. The comprehensive recovery rate of lithium and iron is greater than 95%, and the product purity reaches 99.6%. It is suitable for industrial applications, reduces production costs and realizes Zero discharge of wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118083A_ABST
    Figure CN119118083A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of waste battery recovery, and particularly relates to a method for preparing battery-grade iron phosphate and lithium carbonate from a waste positive electrode material. The method disclosed by the invention comprises the following steps: (1) acid leaching; (2) extracting to remove copper; (3) removing aluminum with ammonium sulfate; (4) adjusting the iron-phosphorus ratio, oxidizing and synthesizing iron phosphate; (5) aging, washing with phosphoric acid and washing with pure water; (6) drying and calcining the iron phosphate to prepare battery-grade iron phosphate; (7) lime impurity removal and deamination; (8) evaporating and concentrating to extract lithium, precipitating lithium with sodium carbonate, and washing; and (9) carbonizing, removing calcium and magnesium from the resin, pyrolyzing and drying to prepare the battery-grade lithium carbonate. The method can realize comprehensive recovery of iron, phosphorus, lithium, aluminum, copper and other valuable elements in the waste lithium iron phosphate positive electrode material, can realize cyclic utilization of ammonia water, and can realize zero discharge of wastewater through evaporation concentration and solution cyclic recovery. The method is high in valuable metal recovery rate, and the comprehensive recovery rates of lithium and iron are both greater than 95%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of recycling waste lithium-ion batteries, and in particular to a method for preparing battery-grade iron phosphate and lithium carbonate from waste positive electrode materials. Background Art

[0002] With the rapid development of the new energy vehicle industry, the use of lithium iron phosphate batteries has increased significantly. Recycling lithium iron phosphate can effectively reduce the demand for primary resources and reduce the damage to the environment caused by resource mining. For example, lithium resources are unevenly distributed around the world. Recycling can increase the self-sufficiency rate of resources and reduce dependence on imports. Environmental protection: Waste lithium iron phosphate batteries contain harmful substances, such as heavy metals. If they are discarded or handled improperly, they will cause serious pollution to soil, water sources, etc. The effective recycling of waste lithium iron phosphate batteries can avoid these potential environmental hazards. Economic benefits: With the advancement of technology and the expansion of market scale, through reasonable recycling and treatment methods, the efficient recovery of lithium carbonate and iron phosphate in lithium iron phosphate batteries can create very considerable economic value. At the same time, reducing resource waste itself also has economic significance.

[0003] At present, there are two main methods for recycling waste lithium iron phosphate batteries: wet recycling and physical recycling. Wet recycling is the common technical route for lithium iron phosphate batteries used by domestic power battery recycling companies. This method uses chemical reactions to dissolve the valuable metal elements in waste lithium iron phosphate batteries into the solution, and then recovers lithium, iron and other elements through a series of separation, purification and other operations. Its advantages are high recycling efficiency and relatively mature technology, but it may produce certain wastewater, waste residues, etc. that need to be treated. Physical recycling mainly processes waste lithium iron phosphate batteries through physical means such as mechanical crushing and screening to separate different material components, such as metal casings, electrode materials, etc. The physical method has relatively low costs, but the purity and efficiency of the recovery may not be as good as the wet method.

[0004] Wet recovery mainly includes selective recovery (prioritized lithium extraction) and full recovery. The current wet recovery technology for waste lithium iron phosphate batteries has the following difficulties in actual production: (1) In the selective recovery process, crude iron phosphate needs to consume a large amount of acid to dissolve, and the subsequent preparation of iron phosphate precipitation from iron phosphate solution will also consume a large amount of alkali, and a large amount of phosphoric acid conversion is required; (2) The full recovery process has a large pressure of impurity removal, and the impurity removal effect will affect the quality of the obtained lithium carbonate and iron phosphate; it is difficult to achieve a high recovery rate of valuable metals; the entire full recovery process has a large amount of solution, and it is necessary to consider the whereabouts of the solution during the production process and wastewater treatment.

[0005] In view of the various problems existing in the existing technology for recycling waste lithium iron phosphate positive electrode materials, there is an urgent need to develop a method with high practical application value, low processing cost and full recovery of iron phosphate and lithium carbonate from waste lithium iron phosphate positive electrode materials. Summary of the invention

[0006] In view of the problems of high pressure of impurity removal, low recovery rate of valuable metals and large amount of process solution in the full recovery process of waste lithium iron phosphate positive electrode materials, the present invention provides a method for preparing battery-grade iron phosphate and battery-grade lithium carbonate using waste lithium iron phosphate positive electrode materials, the method comprising the following steps: (1) acid leaching; (2) extraction and copper removal; (3) ammonium sulfate aluminum removal; (4) adjusting the iron-phosphorus ratio, oxidation, and iron phosphate synthesis; (5) aging, phosphoric acid washing, and pure water washing; (6) drying and calcining iron phosphate to prepare battery-grade iron phosphate; (7) lime impurity removal and deamination; (8) evaporation and concentration to extract lithium, sodium carbonate lithium precipitation, and washing; (9) carbonization, resin calcium and magnesium removal, pyrolysis, and drying to prepare battery-grade lithium carbonate. The method adopts a wet full recovery process to treat waste lithium iron phosphate positive electrode materials, which can realize the comprehensive recovery of valuable elements such as iron, phosphorus, lithium, and copper in waste lithium iron phosphate positive electrode materials, realize the recycling of ammonia water, and achieve zero wastewater discharge through evaporation and concentration and solution recycling. The method has a high recovery rate of valuable metals, and the comprehensive recovery rates of lithium and iron are both greater than 95%. The method is simple in process, easy to operate, and has a good impurity removal effect. It can obtain battery-grade iron phosphate and battery-grade lithium carbonate products with good performance and high quality. The purity of battery-grade iron phosphate and battery-grade lithium carbonate is above 99.6%, which is suitable for industrial application.

[0007] The present invention can be implemented by the following technical solutions:

[0008] The present invention discloses a method for preparing battery-grade iron phosphate and lithium carbonate from waste positive electrode materials, comprising the following steps:

[0009] (1) Alkaline leaching to remove aluminum: crushing the waste lithium iron phosphate positive electrode material to obtain lithium iron phosphate positive electrode powder; adding sulfuric acid solution to the lithium iron phosphate positive electrode powder for acid leaching, and filtering after the acid leaching to obtain acid leaching solution and graphite slag;

[0010] (2) Extraction and copper removal: The acid leaching solution obtained in step (1) is subjected to copper extraction using a ZJ980 copper extractant to obtain a copper-removed solution and a high-purity copper sulfate solution, which can be used to produce cathode copper;

[0011] (3) removing aluminum with ammonium sulfate: adding ammonium sulfate to the copper-removed liquid obtained in step (2) to remove aluminum, thereby obtaining a dealuminized liquid and dealuminized slag;

[0012] (4) Adjusting the iron-phosphorus ratio, oxidation, and synthesizing iron phosphate: adding ammonium dihydrogen phosphate to the dealuminized solution to adjust the iron-phosphorus molar ratio of the solution to 1:1-1.05, then adding hydrogen peroxide for oxidation, and then adding an ammonia solution to synthesize iron phosphate precipitation by controlling the pH of the solution. After the reaction is completed, an iron phosphate slurry is obtained;

[0013] (5) Aging, phosphoric acid washing, and pure water washing: the iron phosphate slurry obtained in step (4) is aged at high temperature, and the aged slurry is filtered to obtain an aged liquid and an aged iron phosphate slag; the aged iron phosphate slag is washed with phosphoric acid and washed with pure water for multiple times, and filtered to obtain washed iron phosphate;

[0014] (6) Drying and calcining the iron phosphate to prepare battery-grade iron phosphate: The iron phosphate obtained in step (5) is dried and calcined to obtain a battery-grade iron phosphate product;

[0015] (7) Lime removal and deammoniation: adding lime milk to the aged solution obtained in step (5) to remove impurities such as iron, phosphorus, and silicon from the solution, and at the same time remove ammonium ions from the solution to avoid the reaction of ammonium ions with sodium carbonate during lithium precipitation and the consumption of a large amount of sodium carbonate;

[0016] (8) Evaporation and concentration to extract lithium, sodium carbonate precipitation of lithium, and washing: The impurity-removed liquid obtained in step (7) is evaporated and concentrated, and deep deammoniation and decalcification are performed to obtain a lithium-rich liquid with a lithium concentration of 15 to 20 g / L; sodium carbonate solution is added to the lithium-rich liquid to synthesize crude lithium carbonate, and the crude lithium carbonate is then washed with pure water;

[0017] (9) Carbonization, resin calcium and magnesium removal, pyrolysis, and drying: The crude lithium carbonate obtained in step (8) is slurried with water at a certain liquid-to-solid ratio, and then carbon dioxide is introduced for carbonization, and filter pressing is performed to obtain a carbonized liquid and calcium carbonate residue; the carbonized liquid is passed through a calcium and magnesium removal resin to deeply remove calcium and magnesium from the solution; the calcium and magnesium removal liquid is subjected to high-temperature pyrolysis and drying to obtain battery-grade lithium carbonate.

[0018] Preferably, the concentration of the sulfuric acid solution in step (1) is 2 to 5 mol / L, the liquid-to-solid ratio is 3 to 6 mL / g, the acid leaching temperature is 25° C., and the acid leaching time is 2 to 6 h.

[0019] Preferably, the concentration of ammonium sulfate in step (3) is 10-15%, the reaction temperature is 30-60° C., the reaction pH is controlled to be 0.5-1.0, and the reaction time is 0.5-1 h.

[0020] Preferably, the amount of hydrogen peroxide in step (4) is 1.5 to 3 times the theoretical amount based on the molar amount of iron, and the oxidation time is 1 to 3 hours; the concentration of the ammonia solution is 5 to 15%, the pH of the iron phosphate synthesis is controlled to be 1 to 3, the reaction time is 1 to 4 hours, and the reaction temperature is 25°C.

[0021] Preferably, the aging temperature of the iron phosphate slurry described in step (5) is 60-100°C, and the aging time is 8-16h; after aging, the iron phosphate slag is slurried by adding pure water at a liquid-to-solid ratio of 5-10mL / g, the temperature of phosphoric acid washing is 50-80°C, and the washing time is 1-3h; the iron phosphate slag after phosphoric acid washing is slurried by adding pure water at a liquid-to-solid ratio of 5-10mL / g, the number of pure water washings is 2-5 times, the temperature of each pure water washing is 50-80°C, and the time of each pure water washing is 1-4h.

[0022] Preferably, the drying temperature of the iron phosphate described in step (6) is 70-100° C., and the drying time is 8-16 hours; the calcination temperature of the iron phosphate is 500-700° C., and the calcination time is 1-4 hours.

[0023] Preferably, the concentration of lime milk described in step (7) is 20-30%, the pH of impurity removal and deamination is 10-14, the temperature of impurity removal and deamination is 70-100° C., the time of impurity removal and deamination is 1-4 hours, and the ammonia gas after deamination is absorbed by an absorption tower, and the absorbed ammonia water can be returned to the iron phosphate synthesis process for recycling.

[0024] Preferably, the temperature for evaporating and concentrating the impurity-removed liquid to extract lithium in step (8) is 70-100°C; the amount of sodium carbonate added is 1-2 times the theoretical amount based on the molar amount of lithium, the concentration of the sodium carbonate solution is 200-400 g / L, the lithium precipitation temperature is 70-100°C, and the lithium precipitation time is 1-4 h; the crude lithium carbonate is washed 2-5 times at a temperature of 70-100°C.

[0025] Preferably, the crude lithium carbonate described in step (9) is added to pure water at a liquid-to-solid ratio of 15-30 mL / g to form a slurry and then carbonized; the liquid pyrolysis temperature after calcium and magnesium removal is 70-100° C., and the pyrolysis time is 1-4 h; the lithium carbonate drying temperature is 70-100° C., and the drying time is 1-4 h.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] (1) The technical solution of the present invention efficiently separates and recovers useful metal elements such as aluminum and copper in waste lithium iron phosphate positive electrode materials through processes such as acid leaching, extraction for copper removal, and ammonium sulfate for aluminum removal. The generated graphite slag can be used to recover conductive graphite; the introduction of sodium ions is avoided and the generation of iron hydroxide and basic ferric sulfate is reduced by using processes such as oxidation, synthesis of iron phosphate, aging, phosphoric acid washing, pure water washing, drying, and calcination. At the same time, the residual ammonium ions in the synthesized iron phosphate slag are gradually removed with washing and calcination, thereby achieving the purpose of deep impurity removal of iron phosphate and obtaining a high value-added battery-grade iron phosphate product.

[0028] (2) The technical solution of the present invention adopts lime impurity removal and deamination, evaporation concentration to extract lithium, sodium carbonate lithium precipitation, carbonization, resin calcium and magnesium removal, pyrolysis, drying and other processes to deeply remove phosphorus, iron, silicon, ammonium, calcium, magnesium and other elements from the lithium-containing aged liquid, which not only achieves deep impurity removal and concentration of the lithium-containing aged liquid, but also achieves zero discharge of wastewater, and can obtain high value-added battery-grade lithium carbonate products.

[0029] (3) The ammonia water produced by the lime impurity removal and deammoniation process of the technical solution of the present invention can be returned to the iron phosphate synthesis process for recycling, which greatly reduces the consumption of ammonia water and effectively reduces the production cost of recycling waste lithium iron phosphate batteries.

[0030] (4) The solution of the technical solution of the present invention can be recycled, and the recovery rate of valuable elements is high. The comprehensive recovery rates of lithium and iron are both greater than 95% based on the valuable metals in the waste lithium iron phosphate positive electrode material.

[0031] (5) The technical solution of the present invention has a simple process flow, is easy to operate, has a good impurity removal effect, has high product purity and good performance, and the purity of battery-grade iron phosphate and battery-grade lithium carbonate is above 99.6%, which is suitable for large-scale production and has obvious economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The specific embodiments of the present invention are further described in detail below with reference to the accompanying drawings, wherein:

[0033] Figure 1 is a process flow chart of the present invention;

[0034] Figure 2 This is the SEM morphology of the battery-grade iron phosphate described in Example 1 of the present invention;

[0035] Figure 3 This is the SEM morphology of the battery-grade iron phosphate described in Example 2 of the present invention. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing battery-grade iron phosphate and battery-grade lithium carbonate by using waste lithium iron phosphate positive electrode materials, comprising the following steps:

[0037] (1) Acid leaching: crushing the waste lithium iron phosphate positive electrode material to obtain lithium iron phosphate positive electrode powder; adding sulfuric acid solution to the lithium iron phosphate positive electrode powder for acid leaching, and filtering after the acid leaching to obtain acid leaching solution and graphite slag;

[0038] (2) Extraction and copper removal: The acid leaching solution obtained in step (1) is subjected to copper extraction using ZJ980 copper extractant to obtain a copper-removed solution and a copper sulfate solution.

[0039] (3) Removal of aluminum by ammonium sulfate: ammonium sulfate is added to the copper-removed liquid obtained in step (2) to remove aluminum, thereby obtaining a dealuminized liquid and dealuminized slag.

[0040] (4) Adjusting the iron-phosphorus ratio, oxidation, and synthesizing iron phosphate: adding ammonium dihydrogen phosphate to the dealuminized solution to adjust the iron-phosphorus molar ratio of the solution to 1:1-1.05, then adding hydrogen peroxide for oxidation, and then adding ammonia solution to synthesize iron phosphate precipitation by controlling the pH of the solution. After the reaction is completed, an iron phosphate slurry is obtained.

[0041] (5) Aging, phosphoric acid washing, and pure water washing: The iron phosphate slurry obtained in step (4) is aged at high temperature, and the aged slurry is filtered to obtain an aged liquid and an aged iron phosphate slag; the aged iron phosphate slag is washed with phosphoric acid, washed with pure water for multiple times, and filtered to obtain washed iron phosphate.

[0042] (6) Drying and calcining the iron phosphate to prepare battery-grade iron phosphate: The iron phosphate obtained in step (5) is dried and calcined to obtain a battery-grade iron phosphate product.

[0043] (7) Lime removal and deammoniation: Lime milk is added to the aged solution obtained in step 5) to remove impurities such as iron, phosphorus, and silicon from the solution, and ammonium ions from the solution to avoid the reaction of ammonium ions with sodium carbonate during lithium precipitation and the consumption of a large amount of sodium carbonate.

[0044] (8) Evaporation and concentration to extract lithium, sodium carbonate precipitation of lithium, and washing: The impurity-removed liquid obtained in step (7) is evaporated and concentrated, and deep deammoniation and decalcification are performed to obtain a lithium-rich liquid with a lithium concentration of 15 to 20 g / L; sodium carbonate solution is added to the lithium-rich liquid to synthesize crude lithium carbonate, and the crude lithium carbonate is then washed with pure water.

[0045] (9) Carbonization of crude lithium carbonate, resin decalcification and magnesium removal, pyrolysis and drying: The crude lithium carbonate obtained in step (8) is slurried with water at a certain liquid-to-solid ratio, and then carbonized by introducing carbon dioxide, and filtered to obtain a carbonized liquid and calcium carbonate residue; the carbonized liquid is passed through a calcium and magnesium removal resin to deeply remove calcium and magnesium from the solution; the calcium and magnesium removal liquid is subjected to high-temperature pyrolysis and dried to obtain battery-grade lithium carbonate.

[0046] The following examples illustrate the present invention in detail.

[0047] Embodiment 1:

[0048] The waste lithium iron phosphate positive electrode material is crushed to obtain lithium iron phosphate positive electrode powder, the main element content of which is as follows: Li 3.89%, Fe 29.68%, Al 1.12%, P 16.42%, and Cu 1.05%.

[0049] (1) Acid leaching:

[0050] The lithium iron phosphate positive electrode powder was added to a 2.5 mol / L sulfuric acid solution at a liquid-solid ratio of 5 mL / g for acid leaching at a temperature of 25°C for 3 h. After the acid leaching, the acid leaching residue and graphite residue were obtained by filter pressing.

[0051] The acid leaching solution was sampled and tested, and the main element contents in the acid leaching solution were as follows: Li 6.26g / L, Fe 48.28g / L, Al2.02g / L, P 26.74g / L, Cu 1.6g / L. The leaching rates of lithium, iron and phosphorus during the acid leaching process were 99.4%, 99.3% and 99.1% respectively.

[0052] (2) Extraction and removal of copper:

[0053] The acid leaching solution is extracted and copper removed by ZJ980 copper extractant to obtain copper-removed solution and high-purity copper sulfate solution. The copper concentration in the copper-removed solution is 0.01g / L, and the high-purity copper sulfate solution can be used to produce cathode copper. The main element contents in the copper-removed solution are as follows: Li 6.13g / L, Fe48.12g / L, Al 1.93g / L, P 25.85g / L, Cu 0.01g / L.

[0054] (3) Ammonium sulfate aluminum removal:

[0055] Add 12% ammonium sulfate solution to the copper removal solution, control the reaction pH to 1.0, the reaction temperature to 30°C, and the reaction time to 1h. After aluminum removal, filter press to obtain aluminum removal solution and aluminum removal slag. The main element contents in the aluminum removal solution are as follows: Li 6.07g / L, Fe 48.01g / L, Al 0.001g / L, P 25.74g / L, Cu 0.01g / L.

[0056] (4) Adjusting the iron-phosphorus ratio, oxidation, and synthesis of iron phosphate:

[0057] Add ammonium dihydrogen phosphate to the dealuminized liquid to adjust the iron-phosphorus molar ratio of the solution to 1:1, then add 30% hydrogen peroxide at twice the theoretical amount based on the molar amount of iron, the oxidation time is 1 hour, and the reaction temperature is 25°C; control the reaction temperature to 25°C, slowly add 5% ammonia solution to the oxidized liquid, control the synthesis pH of iron phosphate to 1.5, and obtain iron phosphate slurry after the reaction is completed.

[0058] (5) Aging, phosphoric acid washing, pure water washing:

[0059] The iron phosphate slurry is aged at high temperature, the aging temperature is 80°C, and the aging time is 10 hours; the aged slurry is filtered to obtain aged liquid and aged iron phosphate slag; the aged iron phosphate slag is slurried by adding pure water at a liquid-solid ratio of 5 mL / g, and then phosphoric acid is added for washing, the phosphoric acid washing temperature is 80°C, and the washing time is 1 hour; the iron phosphate slag after phosphoric acid washing is washed three times by adding pure water at a liquid-solid ratio of 5 mL / g, each pure water washing temperature is 80°C, and each pure water washing time is 1 hour. The slurry after pure water washing is filtered to obtain washed wet iron phosphate.

[0060] Table 1 Comparison of element contents before and after washing of iron phosphate slag after aging

[0061]

[0062] (6) Drying and calcining of iron phosphate to prepare battery-grade iron phosphate:

[0063] The wet iron phosphate is dried at a temperature of 100°C for 8 hours; the dried iron phosphate is calcined at a high temperature of 600°C for 2 hours to obtain a battery-grade iron phosphate product.

[0064] (7) Lime removal and deammoniation:

[0065] Add 25% lime milk to the aged liquid for impurity removal and deammoniation, control the impurity removal and deammoniation pH to 12, the impurity removal and deammoniation temperature to 80°C, and the impurity removal and deammoniation time to 2 hours. The ammonia generated during the deammoniation process is absorbed by an absorption tower, and the absorbed ammonia water can be returned to the ferric phosphate synthesis process for recycling. After the reaction is completed, filter press to obtain lime impurity removal and deammoniation liquid and impurity removal residue.

[0066] Table 2 Element content of the liquid after lime impurity removal and deammoniation

[0067]

[0068]

[0069] (8) Evaporation and concentration to extract lithium, sodium carbonate to precipitate lithium, and washing:

[0070] The liquid after lime impurity removal and deammoniation is evaporated and concentrated for deep deammoniation and decalcification. The temperature for evaporation and concentration of lithium is 100°C. After the reaction is completed, the decalcified residue and lithium-rich liquid with a lithium concentration of 18g / L are obtained by filter pressing. Then, a sodium carbonate solution 1.2 times the theoretical amount of lithium molar amount is added to the lithium-rich liquid for lithium precipitation. The concentration of the sodium carbonate solution is 300g / L, the lithium precipitation temperature is 90°C, and the lithium precipitation time is 1h. After the reaction is completed, the crude lithium carbonate and lithium precipitation mother liquor are obtained by filter pressing. The crude lithium carbonate is washed three times with pure water at a liquid-to-solid ratio of 5mL / g. The temperature of each pure water washing is 80°C, and the time of each pure water washing is 1h. After the pure water washing, the washed crude lithium carbonate and washing water are obtained by filter pressing.

[0071] (9) Carbonization of crude lithium carbonate, removal of calcium and magnesium from resin, pyrolysis, and drying:

[0072] The washed crude lithium carbonate is slurried by adding pure water at a liquid-solid ratio of 25 mL / g, and then carbon dioxide is introduced for carbonization. The carbonization time is 2 hours. After the carbonization is completed, the carbonized liquid and calcium carbonate slag are obtained by filter pressing; the calcium and magnesium in the solution of the carbonized liquid are deeply removed by calcium and magnesium removal resin to obtain a calcium and magnesium removal liquid; the calcium and magnesium removal liquid is subjected to high-temperature pyrolysis, the pyrolysis temperature is controlled to be 100°C, the pyrolysis time is 2 hours, and pyrolysis lithium carbonate and pyrolysis liquid are obtained after the pyrolysis is completed. The pyrolyzed lithium carbonate is dried, the drying temperature is controlled to be 100°C, the drying time is 8 hours, and a battery-grade lithium carbonate product is obtained after the drying is completed.

[0073] Table 3 Element content in battery grade iron phosphate products

[0074]

[0075]

[0076] Table 4 Element content in battery grade lithium carbonate products

[0077] Analyze Project result <![CDATA[Li 2 CO 3 Content, (%)]]> 99.75 Na, (%) 0.01 Mg, (%) 0.001 Ca, (%) 0.001 K,(%) 0.0006 Fe, (%) 0.0007 Zn, (%) 0.0002 Cu, (%) 0.0002 Pb, (%) 0.0001 Si, (%) 0.001 Al,(%) 0.001 Mn, (%) 0.0002 Ni, (%) 0.0008 <![CDATA[SO 4 2- ,(%)]]> 0.007 <![CDATA[Cl - ,(%)]]> 0.001

[0078] Embodiment 2:

[0079] The waste lithium iron phosphate positive electrode material is crushed to obtain lithium iron phosphate positive electrode powder, the main element content of which is as follows: Li 3.11%, Fe 29.32%, Al 1.36%, P 16.23%, and Cu 1.28%.

[0080] (1) Acid leaching

[0081] The lithium iron phosphate positive electrode powder was added to a 3 mol / L sulfuric acid solution at a liquid-solid ratio of 5 mL / g for acid leaching at a temperature of 25°C for 4 hours. After the acid leaching, the acid leaching residue and graphite residue were obtained by filter pressing.

[0082] The acid leaching solution was sampled and tested, and the main element contents in the acid leaching solution were as follows: Li 5.08g / L, Fe 47.96g / L, Al2.58g / L, P 26.21g / L, Cu 1.92g / L. The leaching rates of lithium, iron and phosphorus during the acid leaching process were 99.5%, 99.2% and 99% respectively.

[0083] (2) Extraction and removal of copper:

[0084] The acid leaching solution is extracted and copper removed by ZJ980 copper extractant to obtain copper-removed solution and high-purity copper sulfate solution. The copper concentration in the copper-removed solution is 0.01g / L, and the high-purity copper sulfate solution can be used to produce cathode copper. The main element contents in the copper-removed solution are as follows: Li 4.91g / L, Fe47.82g / L, Al 2.39g / L, P 25.65g / L, Cu 0.01g / L.

[0085] (3) Ammonium sulfate aluminum removal:

[0086] Add 15% ammonium sulfate solution to the copper-removed liquid, control the reaction pH to 0.8, the reaction temperature to 30°C, and the reaction time to 1h. After aluminum removal, filter press to obtain aluminum-removed liquid and aluminum-removed slag. The main element contents in the aluminum-removed liquid are as follows: Li 4.84g / L, Fe 47.73g / L, Al 0.001g / L, P 25.52g / L, Cu 0.01g / L.

[0087] (4) Adjusting the iron-phosphorus ratio, oxidation, and synthesis of iron phosphate:

[0088] Add ammonium dihydrogen phosphate to the dealuminized liquid to adjust the iron-phosphorus molar ratio of the solution to 1:1, then add 30% hydrogen peroxide at 1.6 times the theoretical amount based on the molar amount of iron, the oxidation time is 1 hour, and the reaction temperature is 25°C; control the reaction temperature to 25°C, slowly add 8% ammonia solution to the oxidized liquid, control the synthesis pH of iron phosphate to 2.0, and obtain iron phosphate slurry after the reaction is completed.

[0089] (5) Iron phosphate aging, phosphoric acid washing, pure water washing:

[0090] The iron phosphate slurry is aged at high temperature, the aging temperature is 80°C, and the aging time is 10 hours; the aged slurry is filtered to obtain aged liquid and aged iron phosphate slag; the aged iron phosphate slag is slurried by adding pure water at a liquid-solid ratio of 5 mL / g, and then phosphoric acid is added for washing, the phosphoric acid washing temperature is 80°C, and the washing time is 1 hour; the iron phosphate slag after phosphoric acid washing is washed three times by adding pure water at a liquid-solid ratio of 5 mL / g, each pure water washing temperature is 80°C, and each pure water washing time is 1 hour. The slurry after pure water washing is filtered to obtain washed wet iron phosphate.

[0091] Table 5 Comparison of element contents before and after washing of iron phosphate slag after aging

[0092]

[0093] (6) Drying and calcining of iron phosphate to prepare battery-grade iron phosphate:

[0094] The wet iron phosphate is dried at a temperature of 100°C for 8 hours, and the dried iron phosphate is calcined at a high temperature of 600°C for 2 hours to obtain a battery-grade iron phosphate product.

[0095] (7) Lime removal and deammoniation:

[0096] Add 25% lime milk to the aged liquid for impurity removal and deammoniation, control the impurity removal and deammoniation pH to 11, the impurity removal and deammoniation temperature to 80°C, and the impurity removal and deammoniation time to 2 hours. The ammonia generated during the deammoniation process is absorbed by an absorption tower, and the absorbed ammonia water can be returned to the ferric phosphate synthesis process for recycling. After the reaction is completed, filter presses are obtained to obtain lime impurity removal and deammoniation liquid and impurity removal residue.

[0097] Table 6 Element content of the liquid after lime impurity removal and deammoniation

[0098]

[0099] (8) Evaporation and concentration to extract lithium, sodium carbonate to precipitate lithium, and washing:

[0100] The liquid after lime impurity removal and deammoniation is evaporated and concentrated for deep deammoniation and decalcification. The temperature for evaporation and concentration of lithium is 100°C. After the reaction is completed, the decalcified residue and lithium-rich liquid with a lithium concentration of 20g / L are obtained by filter pressing. Then, a sodium carbonate solution 1.4 times the theoretical amount of lithium molar amount is added to the lithium-rich liquid for lithium precipitation. The concentration of the sodium carbonate solution is 260g / L, the lithium precipitation temperature is 90°C, and the lithium precipitation time is 1h. After the reaction is completed, the crude lithium carbonate and lithium precipitation mother liquor are obtained by filter pressing. The crude lithium carbonate is washed three times with pure water at a liquid-to-solid ratio of 5mL / g. The temperature of each pure water washing is 80°C, and the time of each pure water washing is 1h. After the pure water washing, the washed crude lithium carbonate and washing water are obtained by filter pressing.

[0101] (9) Carbonization of crude lithium carbonate, removal of calcium and magnesium from resin, pyrolysis, and drying:

[0102] The washed crude lithium carbonate is slurried by adding pure water at a liquid-solid ratio of 23 mL / g, and then carbon dioxide is introduced for carbonization. The carbonization time is 2 hours. After the carbonization is completed, the carbonized liquid and calcium carbonate slag are obtained by filter pressing; the calcium and magnesium in the solution of the carbonized liquid are deeply removed by calcium and magnesium removal resin to obtain a calcium and magnesium removal liquid; the calcium and magnesium removal liquid is subjected to high-temperature pyrolysis, the pyrolysis temperature is controlled to be 100°C, the pyrolysis time is 2 hours, and pyrolysis lithium carbonate is obtained after the pyrolysis is completed. The pyrolysis lithium carbonate is dried, the drying temperature is controlled to be 100°C, the drying time is 8 hours, and a battery-grade lithium carbonate product is obtained after the drying is completed.

[0103] Table 7 Element content in battery grade iron phosphate products

[0104] Analyze Project result Iron (Fe), % 36.32 Phosphorus (P), % 20.14 Iron:phosphorus ratio (Fe:P) 0.998 Calcium (Ca), % 0.004 Magnesium (Mg), % 0.0006 Sodium (Na), % 0.008 Potassium (K), % ≤0.001 Copper (Cu), % ≤0.001 Zinc (Cu), % ≤0.001 Manganese (Mn), % ≤0.001 Aluminum (Al), % 0.006 Sulfur (S), % 0.005 Moisture,% 0.12 <![CDATA[Tap density, (g / cm 3 )]]> 0.72 Magnetic foreign matter, % 0.00023 <![CDATA[Particle size (D 50 ),μm]]> 4.87 <![CDATA[Specific surface area, m 2 / g]]> 5.2 Product Appearance Yellow-white powder, no lumps, no agglomerates, no foreign matter

[0105] Table 8 shows the element content in battery-grade lithium carbonate products

[0106] Analyze Project result <![CDATA[Li 2 CO 3 Content, (%)]]> 99.69 Na, (%) 0.008 Mg, (%) 0.001 Ca, (%) 0.001 K,(%) 0.0005 Fe, (%) 0.0007 Zn, (%) 0.0001 Cu, (%) 0.0002 Pb, (%) 0.0001 Si, (%) 0.001 Al,(%) 0.001 Mn, (%) 0.0002 Ni, (%) 0.0008 <![CDATA[SO 4 2- ,(%)]]> 0.008 <![CDATA[Cl - ,(%)]]> 0.001

[0107] The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the technical principles of the present invention. These changes, modifications, substitutions and variations should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing battery-grade iron phosphate and lithium carbonate from waste positive electrode materials, characterized in that: The following steps are involved: (1) Alkaline leaching to remove aluminum: crushing the waste lithium iron phosphate positive electrode material to obtain lithium iron phosphate positive electrode powder; adding sulfuric acid solution to the lithium iron phosphate positive electrode powder for acid leaching, and filtering after the acid leaching to obtain acid leaching solution and graphite slag; (2) Extraction and copper removal: The acid leaching solution obtained in step (1) is subjected to copper extraction using a ZJ980 copper extractant to obtain a copper-removed solution and a high-purity copper sulfate solution, which can be used to produce cathode copper; (3) removing aluminum with ammonium sulfate: adding ammonium sulfate to the copper-removed liquid obtained in step (2) to remove aluminum, thereby obtaining a dealuminized liquid and dealuminized slag; (4) Adjusting the iron-phosphorus ratio, oxidation, and synthesizing iron phosphate: adding ammonium dihydrogen phosphate to the dealuminized solution to adjust the iron-phosphorus molar ratio of the solution to 1:1-1.05, then adding hydrogen peroxide for oxidation, and then adding an ammonia solution to synthesize iron phosphate precipitation by controlling the pH of the solution. After the reaction is completed, an iron phosphate slurry is obtained; (5) Aging, phosphoric acid washing, and pure water washing: the iron phosphate slurry obtained in step (4) is aged at high temperature, and the aged slurry is filtered to obtain an aged liquid and an aged iron phosphate slag; the aged iron phosphate slag is washed with phosphoric acid and washed with pure water for multiple times, and filtered to obtain washed iron phosphate; (6) Drying and calcining the iron phosphate to prepare battery-grade iron phosphate: The iron phosphate obtained in step (5) is dried and calcined to obtain a battery-grade iron phosphate product; (7) Lime removal and deammoniation: adding lime milk to the aged solution obtained in step (5) to remove impurities such as iron, phosphorus, and silicon from the solution, and at the same time remove ammonium ions from the solution to avoid the reaction of ammonium ions with sodium carbonate during lithium precipitation and the consumption of a large amount of sodium carbonate; (8) Evaporation and concentration to extract lithium, sodium carbonate to precipitate lithium, and washing: The impurity-removed liquid obtained in step (7) is evaporated and concentrated, and deep deammoniation and decalcification are performed to obtain a lithium-rich liquid with a lithium concentration of 15 to 20 g / L; Adding sodium carbonate solution to the lithium-rich solution to synthesize crude lithium carbonate, and then washing the crude lithium carbonate with pure water; (9) Carbonization, resin calcium and magnesium removal, pyrolysis, and drying: The crude lithium carbonate obtained in step (8) is slurried with water at a certain liquid-to-solid ratio, and then carbon dioxide is introduced for carbonization, and filter pressing is performed to obtain a carbonized liquid and calcium carbonate residue; the carbonized liquid is passed through a calcium and magnesium removal resin to deeply remove calcium and magnesium from the solution; the calcium and magnesium removal liquid is subjected to high-temperature pyrolysis and drying to obtain battery-grade lithium carbonate.

2. The method for preparing battery-grade iron phosphate and lithium carbonate from waste positive electrode materials according to claim 1, characterized in that: The concentration of the sulfuric acid solution in step (1) is 2-5 mol / L, the liquid-to-solid ratio is 3-6 mL / g, the acid leaching temperature is 25° C., and the acid leaching time is 2-6 h.

3. The method for preparing battery-grade iron phosphate and lithium carbonate from waste positive electrode materials according to claim 1, characterized in that: The concentration of ammonium sulfate in step (3) is 10-15%, the reaction temperature is 30-60° C., the reaction pH is controlled to be 0.5-1.0, and the reaction time is 0.5-1h.

4. The method for preparing battery-grade iron phosphate and lithium carbonate from waste positive electrode materials according to claim 1, characterized in that: The amount of hydrogen peroxide in step (4) is 1.5 to 3 times the theoretical amount based on the molar amount of iron, and the oxidation time is 1 to 3 hours; the concentration of the ammonia solution is 5 to 15%, the pH of the iron phosphate synthesis is controlled to be 1 to 3, the reaction time is 1 to 4 hours, and the reaction temperature is 25°C.

5. The method for preparing battery-grade iron phosphate and lithium carbonate from waste positive electrode materials according to claim 1, characterized in that: The aging temperature of the iron phosphate slurry described in step (5) is 60-100° C., and the aging time is 8-16 hours; after aging, the iron phosphate slag is slurried by adding pure water at a liquid-to-solid ratio of 5-10 mL / g, the temperature of phosphoric acid washing is 50-80° C., and the washing time is 1-3 hours; the iron phosphate slag after phosphoric acid washing is slurried by adding pure water at a liquid-to-solid ratio of 5-10 mL / g, the number of pure water washings is 2-5 times, the temperature of each pure water washing is 50-80° C., and the time of each pure water washing is 1-4 hours.

6. The method for preparing battery-grade iron phosphate and lithium carbonate from waste positive electrode materials according to claim 1, characterized in that: The drying temperature of the iron phosphate described in step (6) is 70-100° C., and the drying time is 8-16 hours; the calcination temperature of the iron phosphate is 500-700° C., and the calcination time is 1-4 hours.

7. The method for preparing battery-grade iron phosphate and lithium carbonate from waste positive electrode materials according to claim 1, characterized in that: The concentration of the lime milk in step (7) is 20-30%, the pH value of impurity removal and deamination is 10-14, the temperature of impurity removal and deamination is 70-100° C., the time of impurity removal and deamination is 1-4 hours, and the ammonia gas after deamination is absorbed by an absorption tower, and the absorbed ammonia water can be returned to the iron phosphate synthesis process for recycling.

8. The method for preparing battery-grade iron phosphate and lithium carbonate from waste positive electrode materials according to claim 1, characterized in that: The temperature for evaporating and concentrating the impurity-removed liquid to extract lithium in step (8) is 70-100°C; the amount of sodium carbonate added is 1-2 times the theoretical amount based on the molar amount of lithium, the concentration of the sodium carbonate solution is 200-400 g / L, the lithium precipitation temperature is 70-100°C, and the lithium precipitation time is 1-4 hours; the crude lithium carbonate is washed 2-5 times at a temperature of 70-100°C.

9. The method for preparing battery-grade iron phosphate and lithium carbonate from waste positive electrode materials according to claim 1, characterized in that: The crude lithium carbonate described in step (9) is added to pure water at a liquid-to-solid ratio of 15-30 mL / g to form a slurry and then carbonized; the liquid pyrolysis temperature after calcium and magnesium removal is 70-100° C., and the pyrolysis time is 1-4 h; the lithium carbonate drying temperature is 70-100° C., and the drying time is 1-4 h.

Citation Information

Patent Citations

  • Method for recovering and recycling waste lithium ion battery cathode material

    CN101555030A

  • Method for recovering lithium in waste and old lithium iron phosphate batteries

    CN106848472A

  • Method for recycling battery-grade iron phosphate and lithium carbonate by using waste lithium iron phosphate battery material

    CN117776133A

  • Method for recycling lithium iron phosphate battery waste

    WO2024021274A1

Cited By

  • Recycling method for positive and negative electrode powder of waste lithium iron phosphate battery

    CN120172431A